Student factors that difficult teaching-learning of research skills - Yamile Andrea Gómez-Delgado; Aldo Bazán-Ramírez; Fredy Hernán Villalobos-Galvis (Interacciones)
The aim of this study was to describe the teachers and students perspective of an educational science center belonging to a public university in Mexico, about factors associated with students, which hinder the teaching-learning process of research skills. The type of study is descriptive. Eight teachers from curricular area of research and seven undergraduate students participated. The technique of data collection was the record of verbal reports; with the teachers were developed individual sessions and with the students were developed a group session. In addition, a documentary review was conducted focusing on the study programs of the research area. The results indicate that the main factors limiting the teaching-learning of science in this context are difficulties in reading and writing skills, disinterest and unfavorable beliefs towards science. The results are analyzed in light of the interbehavioral theory and constitute a contribution to the understanding of the circumstances in which scientific practice is taught and learned in a context in which future teachers are formed.